2015
DOI: 10.1186/s13071-015-0770-0
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of real time PCR to quantify parasite load in serum samples from chronic Chagas disease patients

Abstract: BackgroundInconclusive results of serological diagnosis in Chagas disease have an important impact on blood banks worldwide, reflecting in the high number of discarded bags or in an increased transmission by blood transfusion. Molecular techniques such as qPCR have been used for diagnosis and to monitor Trypanosoma cruzi load in peripheral blood samples. A promising perspective refers to the possibility of parasite DNA detection in serum, taking advantage in using the same samples collected for serological scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 21 publications
6
48
0
5
Order By: Relevance
“…60 Briefly, 5£10 6 splenocytes were stained with CFSE (Life Technologies, C34554) and then incubated with 50 mg/mL Tc24, 5 mg/mL ConA, or media only, 72 hrs, 37 C, 5% CO 2 . Cells were stained with LIVE/DEAD TM Fixable Blue Stain (Life Technologies, L-34961), and then incubated with Purified Rat Anti-Mouse CD16/CD32 (BD Biosciences, 553142).…”
Section: Lymphocyte Proliferationmentioning
confidence: 99%
“…60 Briefly, 5£10 6 splenocytes were stained with CFSE (Life Technologies, C34554) and then incubated with 50 mg/mL Tc24, 5 mg/mL ConA, or media only, 72 hrs, 37 C, 5% CO 2 . Cells were stained with LIVE/DEAD TM Fixable Blue Stain (Life Technologies, L-34961), and then incubated with Purified Rat Anti-Mouse CD16/CD32 (BD Biosciences, 553142).…”
Section: Lymphocyte Proliferationmentioning
confidence: 99%
“…Besides the careful search for parasites in EMB, monitoring for CDR is based on microscopic examination of blood smears and fresh buffy coat preparations, and more recently blood PCR for T cruzi DNA. 5,9,16,17 As non-immunosupressed, chronic chagasic patients can show positive PCR in the blood, 18 probably due to parasite persistence and fortuitous blood circulation, one proposed criterion for the diagnoses of CDR is sequential positive blood PCR results (at least two) of increasing parasitic load. 17 In this study, we showed sequential measurement of T cruzi parasitic load in EMB is useful for the early detection and treatment follow-up of CDR.…”
Section: Discussionmentioning
confidence: 99%
“…Ascaris ascaris worm long, cylindrical and thin ends of the milky white color and flower color. ascaris adult females 20 to 45 cm in length and diameter of 3 to 6 mm and length of 15 to 30 cm shorter female Ascaris male and 2 to 4 mm diameter [6]. Worm egg.…”
Section: Malariamentioning
confidence: 99%
“…Although malaria is suspected as required at any time to collect samples, respecting the time of blood sampling, species and life stages of the parasite makes more possible [8]. The best time for blood in between attacks of chills and fever before, and usually due to the impossibility of finding the parasite in blood samples once collected blood smear should continue until three consecutive days every 6-8 hours [6]. It is clear that the use of anti-malaria drug samples has diagnostic value.…”
Section: Collecting Blood Samplesmentioning
confidence: 99%